Changes and characteristics of 2013's Plan for Territorial Organization of Bogotá, Capital District (2013)
Being the Plan for Territorial Organization (POT) the tool that sets the guideline for municipalities to perform a proper planning for the use of its territory, it’s imperative that this tool be dynamically adjusted to the changes and reality of cities and municipalities on which it has authority. In the case of Bogotá, the Plan for Territorial Organization was approved through Decree 619 of 2000 and subsequently by the decrees 469 of 2003 and 190 of 2004, some minor adjustments were made in its definition, however the city in the last 10 years has experimented a major change at social, economic and infrastructure level which are not reflected consistently in the path traced by the POT of 2000. Through Decree 364 of 2013, the mayor of the city of Bogota, having recourse on articles 12th of Law 810 of 2013 and 8th of Decree 4002 of 2004, proceeded to change the Plan for Territorial Organization, introducing important changes in definition of the course of the capital for the next years, being of vital importance for citizens to know their scope and identify and main points that have been modified.